Farmers’ Perception towards Transformation of Rice-based Cropping System into Tea Garden (Indian Journal of Extension Education, 2021)
Transformation of agricultural lands into non-farm lands or plantations has got tremendous ecological chaos and ripples. Northern part of West Bengal is undergoing rapid changes in rural areas where new opportunities are emerging in the form of demand-driven and market-driven agriculture. Due to persistent low returns from traditional rice cultivation, the transformation of paddy fields into tea gardens has been a recent trend for this part of West Bengal. The present study has been conducted by selecting purposively three blocks from Alipurduar district and sixty respondents through random sampling, those who have already transformed their crop field into tea gardens from these blocks. The farmers’ perception towards transformation is taken as dependent variable along with a score of fourteen independent variables. The responses are collected through a structured interview schedule. The study envisaged that the farmers’ education level, number of family members engaged in the garden, their economic motivation, sources of information, risk orientation behaviour and distance from the tea processing factory showed significant contribution towards the transformation behaviour. The future impact of such transformation on the ecological dynamics in terms of livelihood, biodiversity restoration and ecological resilience can be brought under policy frameworks.